Qaraqalpaq shańaraǴÍ hám neke institutÍnÍń rawajlanÍw basqÍshlarÍ - Utepbergenov, M.A. (SCIENCE and SOCIETY, 2020)
This article deals with the information about the development stages of Karakalpak family and marital relations, several types of Karakalpak marriage and the choice of a bride, a ransom to the bride.